Clinical and program notes. An outbreak of cryptosporidiosis among veterinary science students who work with calves. - Preiser G; Preiser L; Madeo L (Journal of American College Health, 2003)
The authors describe an outbreak of cryptosporidiosis among students working with calves as part of their veterinary science technology program. After an off-campus provider identified an index case, school authorities requested cryptosporidium (crypto) as part of the stool ova and parasite examination of all students presenting to the college health center with significant gastroenteritis. Thirteen students submitted stool specimens that were examined for crypto; 7 were positive, and all were from veterinary science students. One of the calves used in the program also tested positive for crypto. All of the students were immunocompetent and recovered uneventfully. The outbreak was contained by strictly enforcing infectious-disease precautions in the calf barn. The authors recommend considering crypto as a cause of gastroenteritis, especially among farm-animal workers, and urge strict infectious disease precautions for those who attend to livestock.